Effect of flash-calcined sediment substitution in sulfoaluminate cement mortar - Kleib, Joelle; Amar, Mouhamadou; Benzerzour, Mahfoud; Abriak, Nor-Edine (Frontiers in Materials, 2022)
Calcium sulfoaluminate cement is a relatively new type of cement with environmental advantages linked to its low carbon emission. However, there is a lack of knowledge on its use with supplementary cementitious materials. This article aims to study the effect of utilizing the activated flash-calcined sediment from Noyelles-sous-Lens (SC) as a supplementary cementitious material in calcium sulfoaluminate mortar. Therefore, four mixes are prepared by replacing calcium sulfoaluminate cement with 5%, 10%, and 20% of flash-calcined sediment. The reactivity of the cement pastes with and without the sediment is studied by isothermal calorimetry and by measuring the setting time. Then, the mechanical performance is tested at 1, 7, and 28 days. The results show that adding the flash-calcined sediment has an accelerator effect on cement hydration and decreases the induction period. The cumulative heat release and the compressive strength at 28 days are almost the same up to 10% of sediment substitution.